2018
DOI: 10.18034/mjmbr.v5i1.443
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Sensitivity among Isolates of Esherichia coli from Urine Samples in Denizli, Turkey

Abstract: Objective: The research was carried out with isolate and determines the antimicrobial sensitivity in E. coli from urinary tract infections in special hospital in Denizli and recorded at specimens. Methods: Urine samples (n=21) were collected from patients with signs and symptoms of Urinary tract infections. Bacteria were isolated and identified by conventional biochemical profile. Antibiotic resistance pattern of E. coli against different antibiotic was determined by Kirby-Baur method. Results: The results rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…The antimicrobial cephalothin showed a low resistance of 0.6% only. The results are 17.3 consistent and in compliance with previous studies (Inan and Gurler, 2004;Kirac et al, 2016). Attention should be given while prescribing cotrimoxazole, Augmentin, and ampicillin to avoid increasing resistance patterns by E. coli.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The antimicrobial cephalothin showed a low resistance of 0.6% only. The results are 17.3 consistent and in compliance with previous studies (Inan and Gurler, 2004;Kirac et al, 2016). Attention should be given while prescribing cotrimoxazole, Augmentin, and ampicillin to avoid increasing resistance patterns by E. coli.…”
Section: Resultssupporting
confidence: 89%
“…Imipenem has been highly effective against Gram-negative bacteria as shown by several other studies (Mohammed et al, 2016;Bahashwan and Shafey, 2013;Dash et al, 2014;Alam et al, 2017). Aztreonam and ciprofloxacin have been recommended as better antimicrobials against E. coli (Kirac et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that unlike amikacin, ampicillin is not suitable for the treatment of E. coli infections in Iran. Moreover, resistance to carbapenems among isolates collected from Bu-Ali Sina hospital in this study was similar to other studies in Iran and neighboring countries (13,19,21,22,25), while the reported carbapenem resistance rates in non-neighboring countries such as Malaysia and Nigeria were 29.2% and 19.7%, respectively (26,27). This discrepancies may be due to the differences in the type of sample, as Bu-Ali Sina hospital is a specialized pediatric hospital.…”
Section: Discussionsupporting
confidence: 91%
“…An Iranian study performed in 2019 showed that 2.2% of the clinical isolates of E. coli were resistant to this antibiotic (17). However, other studies conducted in Iran 18, Saudi Arabia (12) and Turkey (19), detected no amikacin resistant isolates of E. coli. These results indicate the good e cacy of amikacin as one of the effective antibiotics against infections caused by E. coli.…”
Section: Discussionmentioning
confidence: 99%